Review of studies applying Bronfenbrenner's bioecological theory in international and intercultural education research - Tong, Peiru; An, Irene Shidong (Frontiers in Psychology, 2024)
The Russian-born American psychologist Bronfenbrenner’s bioecological perspective on human development is an ideal framework for understanding how individuals negotiate the dynamic environment and their own identities in international and intercultural education settings. However, a review of the current literature shows that most studies either adopted the earlier version of the theory (i.e., the ecological systems theory) or inadequately presented the most recent developments of the bioecological model (i.e., the process-person-context-time model). The construct of proximal processes – the primary mechanisms producing human development according to Bronfenbrenner – has seldom been explored in depth, which means the true value of bioecological theory is largely underrepresented in international and intercultural education research. This article first presents a review of studies that adopt Bronfenbrenner’s theory and then offers future directions for the scope and design of international and intercultural education research.